Criminal and civil aspects of bribery - Leslie, Andrew Brian (Rhodes University, Faculty of Law, Law, 1988)
The purpose of this work is to identify legal action which may be taken against parties to bribery in the fields of criminal and civil law. In particular, the element of mens rea is investigated with regard to criminal corruption. On the civil side, the principal, who has been the victim of bribery, has various remedies against the parties to the bribe. These remedies are analysed with special reference to the influence of English law on the South African law in this field. The options open to the principal, where his agent has made a secret profit which does not amount to bribery, are also considered.
Keywords: Bribery